2018
DOI: 10.1002/admt.201800350
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Cortical Neurons through Electronic Memristive Synapse

Abstract: A synapse is a biological structure, which connects two neurons enabling specific and unidirectional information flow (excitation or inhibition) from one neuron to another. Synaptic connections are the key elements of the neuronal networks and their plasticity underlies learning and memory. Recent progress in building artificial neuronal networks is largely based on the elements mimicking features of natural synapses in silico or in electrico. [1][2][3] Hybrid networks, in which braincomputer systems read and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 47 publications
0
57
0
Order By: Relevance
“…Despite the large number of available examples, they usually reflect different sides of such interaction and primary confirm some level of connectivity between biological and artificial systems. A functional interface between simple living being (slime mold) and memristor devices has been reported (Adamatzky et al, 2012) and, recently, the possibility of direct synaptic coupling of neuron cells from the rat cortex through a memristive device has been demonstrated (Juzekaeva et al, 2019). Future implementation of this approach requires the development of interrelated solutions at all levels, using both existing and emerging technologies in a single conceptual map matching the requirements for compactness, performance, energy efficiency, speed, reliability, and safety.…”
Section: Memristive Neurohybrid Chip: Concept and Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the large number of available examples, they usually reflect different sides of such interaction and primary confirm some level of connectivity between biological and artificial systems. A functional interface between simple living being (slime mold) and memristor devices has been reported (Adamatzky et al, 2012) and, recently, the possibility of direct synaptic coupling of neuron cells from the rat cortex through a memristive device has been demonstrated (Juzekaeva et al, 2019). Future implementation of this approach requires the development of interrelated solutions at all levels, using both existing and emerging technologies in a single conceptual map matching the requirements for compactness, performance, energy efficiency, speed, reliability, and safety.…”
Section: Memristive Neurohybrid Chip: Concept and Challengesmentioning
confidence: 99%
“…The most interesting direction at the boundaries of neurotechnology and neuromorphic prosthetics has recently emerged thanks to the seminal paper (Juzekaeva et al, 2019), where the main principles and feasibility of a memristive prosthesis of a synapse connecting two not connected via natural synapses neurons of a rat brain slice are proposed. This work triggered the discussion of the option to use stochastic memristive devices of different nature as main building block of neuromorphic prosthesis relocating functions and topology of natural neuronal circuits.…”
Section: Memristive Neural Arcitectures: Toward Neuroprostheticsmentioning
confidence: 99%
“…38 More recently, the same group coupled cortical neurons in brain slices with these organic artificial synapses and showed communication between the neurons mediated by an organicbased synapse. 39 The range of demonstrations where organic electrochemical devices are used in a neuromorphic function is a testament to their versatility and potential in brain-machine interfaces. The biomimicking aspect of polymer-based electrochemical devices was further explored by Lee et al, who fabricated a core-sheath structure reminiscent of a neuron axon.…”
Section: Organic Neuromorphic Devices and Systems: A Brief Historymentioning
confidence: 99%
“…[11][12][13] It was demonstrated the possibility of their utilization as synapse analogs in neuromorphic systems, mimicking parts of nervous system of simple animals (pond snail Lymnaea stagnalis); [14] in systems with frequency-dependent plasticity; [15] circuits, allowing spiketiming-dependent plasticity (STDP) [16] and in circuits, providing synaptic connection between two nervous cells of the rat cortex. [17] However, the limiting factors of the OMDs are low rate of the resistance switching and stability. [18,19] It has been shown that down-scaling of the devices' sizes results in the increase in the ON/OFF switching rate as well as endurance.…”
Section: Introductionmentioning
confidence: 99%